'Ulumul Qur'an: Faedah dan Urgensinya dalam Memahami Firman Tuhan - Syafi'i, Ahmad; Sulkifli, Sulkifli; Bakar, Achmad Abu; Haddade, Hasyim; Darnanengsih (Al-Riwayah : Jurnal Kependidikan, 2023)
The nature of the 'Ulumul Qur'an, its importance, and the necessity of studying it in order to comprehend God's message are all covered in this article. The intention of this article's authoring is to provide knowledge about 'Ulumul Qur'an. The descriptive library research used to write this essay. This study is based on existing literature. The outcome of this study is 'Ulumul Qur'an,' which is a compilation of several scientific arguments that were initially presented separately. The disciplines that are closely connected to the Qur'an are discussed, both in terms of the Qur'an's existence and its comprehension as a set of rules for human life. "Ulumul Qur'an is very helpful in studying and understanding the Qur'an correctly. It can be used to interpret the verses and draw laws and manners from the Qur'an, known as istinbath."The Ulumul Qur'an is a precise tool that interpreters utilize to comprehend Allah SWT's words, helping them avoid interpreting things incorrectly or superficially. Finding the meanings of Qur'anic words, explaining verses and their meanings as well as unclear matters, revealing Qur'anic rulings, and then putting those rules into practice to achieve happiness in this world and the next are the major goals of 'Ulumul Qur'an.